The Influence of Achievement Motivation and The Need for Regular Life on The Formation of The Islamic Personality of IAIN Kudus - Retnanto, Agus; Firdiansyah, Bahtiar; Fah, Lay Yoon (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2023)
The Influence of Achievement Motivation and The Need for Regular Life on The Formation of The Islamic Personality of IAIN Kudus